Ambivalent joint production and the natural environment: an economic and thermodynamic analysis ; with 11 tables - Baumgärtner, Stefan (Physica-Verl., 2000)
Many environmental damages are caused by substances which come into existence asundesired joint outputs in the production of desired goods. Whether an output isdesired or not, however, is not an inherent property of the substance itself butdepends on the context of production. This book studies in an interdisciplinary way the role of the potential ambivalence of joint outputs for the description and analysis of dynamic economy-environment interactions and for the design of environmental policy. Keywords: Joint Production, Enviromental Policy, Thermodynamics Contents: Introduction.- The Phenomenon of Joint Production: Joint Production and the Natural Environment.- Thermodynamics.- All Production is Joint Production.- The Analysis of Joint Production in the History of Economic Thought: The Classical Position and its Early Critics.- The Abandonment of Classical Theory.- Neoclassical Theory from Partial to General Equilibrium Analysis.- The Role of Joint Production for the Construction of Economic Theory.- The Economics of Ambivalent Joint Production: The Concept of Joint Production.- Ambivalence of Joint Products.- Joint Productsand Irreversibility.- Non-Convexity of the Production Set.- Ambivalent Joint Production: Putting the Issue in Perspective.
Literaturverz. S. [295] - 321
Keywords: Hochschulschrift; Umweltökonomie; Wirtschaftstheorie; Kuppelproduktion